Entre o maravilhoso e o fantástico : a vila de Alto Palmital-PR e suas crenças - Silva, Ed Carlos da (2009)
In the process of historical development, which was built up in approximately seven decades (1940 - 2008), the inhabitants of "Alto Palmital" and its surroundings, located in the rural area of "Boa Esperança" town, Central Region of "Paraná" State, developed a complex set of beliefs. These allowed the constitution of many practices, which still have influenced the inhabitants' behavior in the social place. The understanding of this wonderful world, through the collective representation of inhabitants, is the object of this research, whose purpose is to understand how the beliefs contributed to the building and normalization of the instituted collective practices. The theoretical framework used to do this study belongs to the Cultural History area, which is based in the considerations made by Roger Chartier (2002) about collective representations. Having the same objective we also used the concepts of social place and normalization of the instituted practices of Michel de Certeau (2006). Considering these aspects we carried out interviews with 80 residents among a number of 725 people. Therefore, in the treatment oral source our methodological choice was based on Paul Thompson (1992) considerations and in the book organized by Marieta de Moraes Ferreira and Janaina Amado (2006). The collected statements confirm the institution of the investigated beliefs and their relation with the collective practices, through the process of representation and appropriation of the narratives by the community residents. This transmission forms contributed a lot to the development of the history of this place as well as to the definition of the identity of social place.